Dive Deeper into the Nature of Corruption through an Interdisciplinary Lens - Suparman, Omang; Kusuma Dewi, Elya; Anisah Supandi, Tuti (Jurnal Legisci, 2024)
Numerous scholars have conducted interdisciplinary studies from theoretical and empirical viewpoints to tackle the complex corruption issue. Presenting opinions from other disciplines, this study provides a comprehensive and current analysis of the recent literature on corruption. More specifically, the writers clarified corruption by merging viewpoints from several fields, including criminology, psychology, and economics. Through an organized investigation of the origins and effects of corruption at the human, corporate, and societal levels, we may comprehend the elements that lead to corrupt behavior and its substantial influence.